Fair value and environmental disclosure impact on agricultural company financial performance - Muhammad El-barony Haidar Aziz; Ani Wilujeng Suryani; Hazreel Hasmi (Jurnal Akuntansi Aktual, 2023)
AbstractBiological assets are growing assets owned by a company and can provide economic benefits in the future. In Indonesia, biological assets are recorded and recognized based on PSAK 69. The PSAK 69 requires the use of the fair value method to measure biological assets that were previously measured using the historical cost method. This study aims to determine the impact of PSAK 69 implementation on financial performance. This study also investigates the effect of environmental reporting on financial performance. The agricultural listed company on the Indonesia Stock Exchange was chosen as the sample in this quantitative study. The data was obtained from the financial reports from 2015 to 2020. The environmental reporting data was measured by a PROPER rating. The data was then analysed using panel data regression. The findings of this study indicated that the implementation of PSAK 69 did affect the financial performance. The environmental reporting using the PROPER rating however did not affect the financial performance. The result of this study can be used as a basis for decision making for management to improve the company’s financial performance and environmental reporting.AbstrakAset biologis adalah aset bertumbuh yang dimiliki oleh perusahaan dan dapat memberikan manfaat ekonomi di masa mendatang. Di Indonesia, aset biologis dicatat dan diakui berdasarkan PSAK 69 mulai tahun 2018. PSAK 69 meminta aset biologis diukur dengan metode fair value, yang sebelumnya diukur dengan historical cost. Penelitian ini bertujuan untuk mengetahui dampak penerapan PSAK 69 tentang aset biologis terhadap kinerja keuangan. Selain itu, penelitian ini juga ingin mengetahui dampak pelaporan lingkungan pada kinerja keuangan. Penelitian ini merupakan penelitian kuantitatif dengan perusahaan sektor agrikultur yang terdaftar pada Bursa Efek Indonesia sebagai sampelnya. Data penelitian bersumber dari laporan keuangan perusahaan tahun 2015-2020. Data tentang pelaporan lingkungan diambil dari peringkat PROPER. Data diolah dengan menggunakan analisis regresi data panel. Hasil dari penelitian ini menunjukkan bahwa perubahan pengukuran pada aset biologis berpengaruh pada kinerja keuangan perusahaan. Pelaporan lingkungan menggunakan peringkat PROPER tidak berpengaruh terhadap kinerja keuangan perusahaan. Penelitian ini dapat dijadikan dasar pengambilan keputusan bagi manajemen untuk meningkatkan kinerja keuangan perusahaan serta meningkatkan pelaporan lingkungan.